Blood stasis : China's classical concept in modern medicine : including a translation of the seminal work of Wang Qing-Ren 'Corrections of mistakes in the medical world' /: China's classical concept in modern medicine : including a translation of the seminal work of Wang Qing-Ren 'Corrections of mistakes in the medical world'. (2007) - Unknown
No abstract available